2020
DOI: 10.1055/a-1221-9879
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis volume and Choi criteria predict the response to endoscopic ultrasonography-guided HybridTherm ablation of locally advanced pancreatic cancer

Abstract: Background and study aims Endoscopic ultrasound (EUS)-guided ablation of pancreatic ductal adenocarcinoma (PDAC) with HybridTherm-Probe (EUS-HTP) is feasible and safe, but the radiological response and ideal tool to measure it have not been investigated yet. The aims of this study were to: 1) assess the radiological response to EUS-HTP evaluating the vital tumor volume reduction rate, Response Evaluation Criteria in Solid Tumors (RECIST1.1) and Choi criteria; 2) determine the prognostic predictive yield of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…This study confirmed the EUS-HTP safety in PDAC [ 9 , 10 ]. With respect to the other similar monopolar devices performing EUS-guided RFA, despite the less handy 14-gauge diameter the HTP device takes advantage from the bipolar and cooling systems to create larger ablation areas with less power input and less collateral thermal damage than other available EUS-RFA probes.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This study confirmed the EUS-HTP safety in PDAC [ 9 , 10 ]. With respect to the other similar monopolar devices performing EUS-guided RFA, despite the less handy 14-gauge diameter the HTP device takes advantage from the bipolar and cooling systems to create larger ablation areas with less power input and less collateral thermal damage than other available EUS-RFA probes.…”
Section: Discussionsupporting
confidence: 83%
“…As previously described [ 8 , 9 , 10 ], the active tip (26-mm length) of the needle-shaped (14-gauge) HTP was placed directly into target lesion under EUS-guidance using colour power-doppler to avoid vascular structures, and activated at fixed RF power of 18W and cooling pressure of 650 psi, with application time between 240 and 480 s for a 2-cm up to >3-cm mass or until the electric resistance, induced by tumour tissue desiccation and devitalization, increased.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no evidence of vascular thrombosis or injury of the superior mesenteric/portal vein con uence, superior mesenteric artery or common hepatic artery from the RFA. A recent report of a phase-II randomized trial of EUS-RFA for PDAC demonstrated a similar safety pro le [17]. This trial included both borderline resectable or locally-advanced PDAC and was eventually closed as the RFA probe was no longer produced.…”
Section: Discussionmentioning
confidence: 88%